Peran Employee Involvement dan Public Service Motivation, serta Mediasi Affective Commitment Terhadap Perceived Organizational Performance - Yuliani, Fahrina; Sibarani, Sondang E. M.; Ebenheizer, Steven (UI Scholars Hub, 2021)
The government has regulated and legalized the compensation and benefits system through ap- plicable regulations and ratified nationally. However, the public sector needs to consider other non- monetary factors to improve employee performance, such as employee involvement, public service motivation, affective commitment, and perceived organizational performance. This research ques- tionnaire was distributed to public sector employees in an Indonesian government agency totaling 157 respondents, containing closed questions using a six-point Likert scale, an online survey plat- form, and processed using the Lisrel SEM method. This study was conducted to clarify the influence of previously identified and discussed individual-level factors as essential determinants of organiza- tional performance. Public sector managers must know better ways to manage and improve employee attitudes by paying attention to employee involvement, public service motivation, and affective com- mitment to improving organizational performance. The result of this study indicates that prioritizing employee involvement in HR management practices in the public sector has a significant impact on affective commitment and perceived organizational performance. However, in this study, the role of public service motivation has no impact both towards affective commitment and perceived organiza- tional performance, which is quite contradictory to some findings from previous studies.